PERTUMBUHAN BIBIT KARET (Hevea brasiliensis) OKULASI PADA MEDIA CAMPURAN SUBSOIL DENGAN PUPUK ORGANIK - Nelly Winda Saragih; Sampoerno '; Islan ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Rubber tree (Hevea brasiliensis) is one of the strategic agricultural commodities for the economy in Indonesia, both in increasing revenue planters, providing jobs for residents, preserve the environment and also as a source of foreign exchange. The use of the subsoil is expected to produce good growth of rubber seedlings which when mixed application of organic fertilizers. Through the use of organic fertilizers is expected to increase the holding power of water, nutrients and repair donated soil aggregates. This study experimentally using a completely randomized design (CRD) consisting of 5 treatments and 5 replicates so entirely as many as 25 experimental units. Each unit consists of 2 plants as well as a sample, so that the overall number of 50 plants. Data obtained from the results of the study were statistically analyzed using analysis of variance (ANOVA) followed by test Honestly Significant Difference (HSD) at the 5% level. Parameters measured were seedling height increment (cm), stem diameter increment (cm), in the number of leaves (strands), root length (cm), root volume (ml), seedling dry weight (g) and the ratio of the root crown. The mixture of subsoil with organic fertilizer oil palm empty fruit bunches of the best shows on rubber seedlings (Hevea brasiliensis). Keywords: Rubber, Organic Fertilizer, media on grafting subsoil